The Effects of GA3 Application on the Quality of ‘Kediri Kuning’ Variety of Grape (Vitis vinifera L.) - Ni Nyoman Ari Mayadewi (Universitas Panji Sakti, 2023)
‘Kediri Kuning’ is one of the superior varietiy in Indonesia. Fruit quality is an important thing that must be considered. This research reports the effects of GA3 on the quality of ‘Kediri Kuning’ variety of grape. This experiment employed a randomized block design, five treatments, and seven replications. Meanwhile, the treatments employed GA3 concentrations of 0, 25, 50, 75, and 100 ppm. The GA3 was applied by spraying GA3 in inflorescence twice before anthesis, namely on days 14 and 28 after production pruning. Data was analyzed using analysis of variance and the differences between treatment means were analyzed using Least Significant Difference (LSD). This study revealed that GA3 25-100 ppm could more significantly increase fruit sugar content at harvest, fruit length, and fruit diameter than the control group. Seed weight at a concentration of 100 ppm is lower and more statistically significant than that at other treatments. However, all treatments could not induce seedless because the seed remains in the fruit.